2013
DOI: 10.1177/1756283x13492580
|View full text |Cite
|
Sign up to set email alerts
|

Interest in medical therapy for celiac disease

Abstract: Most individuals with celiac disease are interested in using a medication. Interest was highest among men, older individuals, frequent restaurant customers, individuals dissatisfied with their weight or concerned with the cost of a gluten-free diet, and those with a worse quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
2
26
0
2
Order By: Relevance
“…Stevens & Rashid (5) Canada Cereal-based General grocery stores On average, gluten-free products were 242% more expensive than regular products 3 Singh & Whelan (6) UK Cereal-based Noncereal-based…”
Section: Discussionmentioning
confidence: 99%
“…Stevens & Rashid (5) Canada Cereal-based General grocery stores On average, gluten-free products were 242% more expensive than regular products 3 Singh & Whelan (6) UK Cereal-based Noncereal-based…”
Section: Discussionmentioning
confidence: 99%
“…Patients both in the United States [2] and England [3] have indicated that they are dissatisfied with the gluten-free diet and would like the availability of additional therapies. A glutenase preparation (latiglutenase) was tested in a large trial that failed to fulfil the primary endpoint of mucosal healing.…”
Section: Discussionmentioning
confidence: 99%
“…In genetically susceptible individuals, intestinal inflammation is triggered by the ingestion of gluten derived from cereals such as wheat, rye, or barley, leading to crypt hyperplasia and villous atrophy. Although patients want additional therapies [2,3], the only treatment currently available consists of a gluten-free diet (GFD).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Celiac Dietary Assessment tool (CDAT) is the most widely used scoring system. The CDAT is a seven-item questionnaire that has been used and validated in six studies to date, involving 1855 patients (35,44,(46)(47)(48)(49) . The CDAT has yet to be compared to histology for adherence but was found to correlate highly with dietetic evaluations for assessing adherence (44) .…”
Section: Adherence Scoresmentioning
confidence: 99%